Recognition in relationships between young people with cognitive disabilities and support workers. (September 2020) - Robinson, Sally; Blaxland, Megan; Fisher, Karen R.; Johnson, Kelley; Kuang, Caiyue; Graham, Anne; Neale, Kate
Highlights: How young people with cognitive disability and support workers work together influences their identities and wellbeing. Interpersonal recognition is mutually experienced by the young people and workers. Organisations need to foster mutual recognition through practices that demonstrate caring, respect and valuing. Online surveys for young people with disability can be made accessible. Abstract: The research used Honneth's interpersonal recognition theory (caring about, respecting and valuing), mediated by the institutional context, to explore how young people with cognitive disabilities and support workers view the quality of their relationship. Such understanding can inform improvements to how they work together and can influence their identities and wellbeing. Separate online surveys for young people with cognitive disabilities (81) and paid workers (56) were developed based on earlier findings from in-depth qualitative research. Most respondents experienced recognition within their support relationships. The recognition positively related to the length of the relationship and differed by characteristics such as location. The findings suggest that recognition was mutually experienced by the young people and workers. The findings draw attention to the ways social services might foster mutual recognition by promoting practices that demonstrate caring, respect and valuing. They might advocate for policy that highlights mutual recognition in paid support.